Prediction of sensorial properties (colour and taste) of amala, a paste from yam chips flour of West Africa, through flour biochemical properties - Mestres, Christian; Dorthe, Sandrine; AKISSOE, H. NOËL; HOUNHOUIGAN, DJIDJOHO JOSEPH (My University, 2004)
Color and taste are permanent features of amala, a traditional thick paste obtained from yam chips flour. To assess these attributes, 23 yam chips presenting various quality attributes were processed. The sensory attributes of their derived amala were determined and some biochemical characteristics of yam flours measured. A panel defined five main taste attributes for amala: sweetness, bitterness, acidity, fermented, and roasted tastes. Amala color was measured instrumentally and sensory scores were highly correlated with flour biochemical analyses; amala sweetness was positively correlated with glucose and fructose content of the flour, whereas amala acidity and fermented taste were linked to organic acids and lactic acid contents of flour, respectively. In addition, darkness, bitterness, and roasted tastes of amala could be tightly predicted by multiple regression analysis from phenolic compound and glucose–fructose contents. Phenolic content of yam flour plays thus a key role on sensorial quality of amala. However, polyphenol oxidase and peroxidase activities were almost null in yam flours and their specific role on yam flour phenolic content needs to be clarified
Keywords: Biochemical composition; Dioscorea spp.; Flour; Sensorial; analysis; Yam